Kinanthropometry and body composition: A natural home for three-dimensional photonic scanning - Stewart, A. D. (Journal of Sports Sciences, 2010)
Überblicksbeitrag zur Methode dreidimesionaler Foto-Scan-Methoden des Körperbaus.